France : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This Selected Issues paper analyzes developments and issues in banking and financial markets in France. The paper provides an overview of the transition from a state-directed to a market-based financial system. It adopts a comprehensive approach and discusses the outcome of this transition in banking, insurance, and capital markets. The paper highlights the sequencing of financial sector modernization. The analysis concludes that, on balance, France has successfully modernized its financial industry and the financial system seems better prepared to operate successfully in the increasingly competitive international environment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet